PROJECT LEARNDEMIC (Learning Assessment and Reading Development through Enhanced Modified Intervention and Collaboration) - D. Engada , Johnny; Maguate, Guarin (International Journal of Scientific Research and Management (IJSRM), 2023)
The CoViD-19 pandemic has brought serious impact to the various sectors of society especially in education where teachers experience difficulties in the teaching-learning process with their learners. Due to lack of internet connection, teachers of Ansulag Elementay School opted to use modular distance learning delivery mode where learners have to answer every activity or learning task provided in their module at home and submit such to their teacher as scheduled without the usual teacher-learner interactions. This affect learners’ access to quality instruction that affect their learning outcome. Thus, the learning gap between the abilities that learners would have developed in the context of standard educational practice and their actual learning is significantly noted.  In line with the 2021 National Reading Month was themed “Bawat Bata Bumabasa Sa Kabila ng Hamon ng Pandemya,” (Every Child Reading Despite the Challenge of the Pandemic) as per DepEd Memorandum No.348, s.2021, the innovators crafted a reading innovation which is the Project LEARNDEMIC (Learning Assessment and Reading Development through Enhanced Modified Intervention and Collaboration). This is aligned with ECARP- Every Child A Reader Program, 3Bs or Bawat Bata Bumabasa, the Regional Innovation banner program: LIBRO or Literacy Initiatives Bridging Reading Opportunities and the division banner program E-RENE (Enhancement of REading and Numeracy towards Excellence). All these initiatives is in support to the DepEd’s mission and vision as well as the regional mantra that every child a champion as per RM Order No.753 s.2021.